The Immortal Crown : An Age of X Novel - Mead, Richelle (Mead, Richelle. Age of X., 2014)
"The #1 New York Times bestselling author of the Vampire Academy and Bloodline series returns with the second installment in her acclaimed Age of X series. Gameboard of the Gods introduced religious investigator Justin March and Mae Koskinen, the beautiful supersoldier assigned to protect him. Together they have been charged with investigating reports of the supernatural and the return of the gods, both inside the Republic of United North America and out. With this highly classified knowledge comes a shocking revelation: Not only are the gods vying for human control, but the elect-special humans marked by the divine-are turning against one another in bloody fashion. Their mission takes a new twist when they are assigned to a diplomatic delegation headed by Lucian Darling, Justin's old friend and rival, going into Arcadia, the RUNA's dangerous neighboring country. Here, in a society where women are commodities and religion is intertwined with government, Justin discovers powerful forces at work, even as he struggles to come to terms with his own reluctantly acquired deity. Meanwhile, Mae-grudgingly posing as Justin's concubine-has a secret mission of her own: finding the illegitimate niece her family smuggled away years ago. But with Justin and Mae resisting the resurgence of the gods in Arcadia, a reporter's connection with someone close to Justin back home threatens to expose their mission-and with it the divine forces the government is determined to keep secret"--